2019
DOI: 10.1177/1708538119847390
|View full text |Cite
|
Sign up to set email alerts
|

The association between platelet/lymphocyte ratio, neutrophil/lymphocyte ratio, and carotid artery stenosis and stroke following carotid endarterectomy

Abstract: Objectives Platelet/lymphocyte ratio is considered to be a recent biomarker which is not only related with inflammation but also associated with the atherosclerotic process. In this study, we aimed to investigate the relationship between carotid artery stenosis, platelet/lymphocyte ratio, neutrophil/lymphocyte ratio, and mean platelet volume in patients undergoing carotid endarterectomy. Methods A total of 160 patients (127 males, 33 females; mean age 69.98 ± 9.76 years; range 48–92 years), who were undergoing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 28 publications
0
28
1
Order By: Relevance
“…In another study, high PLR values could indirectly estimate the infarcted size of stoke patients and the poor recanalization rate after thrombectomy therapy (13). Last, an increased PLR has also been shown to play an important role in postoperative stroke after carotid endarterectomy and the development of post-stroke depression (PSD) (37, 38). However, the association between PLR and the prognosis of AIS patients treated with IVT has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, high PLR values could indirectly estimate the infarcted size of stoke patients and the poor recanalization rate after thrombectomy therapy (13). Last, an increased PLR has also been shown to play an important role in postoperative stroke after carotid endarterectomy and the development of post-stroke depression (PSD) (37, 38). However, the association between PLR and the prognosis of AIS patients treated with IVT has not yet been studied.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are some studies such as monitoring the severity of carotid artery disease and the development of symptoms, and predicting the development of stroke with the PLR value [20,21]. In addition to platelets, it has been shown that neutrophils and lymphocytes play a decisive role in the development of symptoms, especially in stroke, in patients under medical follow-up and in patients undergoing carotid endarterectomy [22]. In our study, we found that NLR and PLR values were correlated with symptom development.…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the recent publication of Des¸er et al reporting the association between platelet/ lymphocyte ratio (PLR), neutrophil/lymphocyte ratio (NLR), and carotid artery stenosis and stroke following carotid endarterectomy. 1 The authors found a significant correlation between the degree of ICA stenosis and the NLR (r ¼ 0.258, p < 0.01). Other studies have shown that the NLR was significantly higher in symptomatic patients with ICA stenosis compared to nonsymptomatic patients, 2,3 suggesting the interest of the NLR as a potential predictor for ICA plaques to become symptomatic.…”
mentioning
confidence: 92%
“…4 The originality of the study published by Des¸er et al was to investigate the interest of the PLR as a predictive factor of the post-operative outcomes of patients undergoing endarterectomy. 1 Interestingly, they found that the PLR was an independent predictive factor of post-operative stroke (p ¼ 0.047). A PLR value >145.3 had a sensitivity and a specificity of 83.3% and 73.8%, respectively, to predict post-operative stroke.…”
mentioning
confidence: 97%